EFEKTIVITAS MODEL PROBLEM POSING DENGAN PENDEKATAN LINGKUNGAN TERHADAP HASIL BELAJAR PADA MATERI HUKUM II NEWTON - Jacobus, Maria Fellycia Meike; Rende, Jeane Cornelda; Tumimomor, Farly (SOSCIED, 2024)
This study aims to determine the effectiveness of using the problem posing learning model with an environmental approach to learning outcomes. This research was conducted at SMA N 1 Likupang, North Minahasa. In this study using one group pretest-posttest design. The instrument in this study used a cognitive description test in the form of a pre-test and posttest to measure student learning outcomes. The sample in this study was class X MIA II which amounted to 20 students. The average pretest score is 50 and the average posttest score is 84.25, the results of the data processing show an increase. The results of the N-Gain Test score 0.7791 which shows that there is an increase in student learning outcomes in the high category with a percentage of 77.90%. Based on this data, it can be concluded that the Problem Posing Learning Model with an Environmental Approach can improve student learning outcomes on the material of Newton's Law II